Meta-Analysis of Enteral Lactoferrin Supplementation for Reducing the Risk of Preterm Infants Sepsis - Supranoto, Yehuda Tri Nugroho; Tanuwijaya, Dini Cynthia Dewi (Smart Medical Journal, 2022)
Introduction: Severe COVID-19 in pregnancy is strongly associated with preterm infant late-onset sepsis (LOS), which is a major cause of morbidity and mortality in infants. Recently, Lactoferrin, an iron-binding protein significantly discovered in human colostrum, shows potential effect on reducing the risk of preterm infant LOS and mortality by its immunomodulatory properties. Therefore, this study aimed to evaluate the effect of Lactoferrin on reducing the risk of preterm LOS, necrotizing enterocolitis (NEC), and mortality in preterm infants. Methods: This study followed the guidelines provided by PRISMA. A literature search was conducted with PubMed, Cochrane Library, Google Scholar, and ScienceDirect. The combined effect of LOS, NEC and mortality incidence were presented as risk ratios (RR) with a 95% confidence interval (CI) using a random-effects model (REM) or fixed-effects model (FEM) forest plot. Furthermore, the heterogeneity level was checked by I2 and the p-value of the chi2 test. Results: The incidence of LOS was significantly higher in the control than lactoferrin supplementation group [RR=0.65, 95% CI (0.56,0.77), p